Guerrilla Girls: the art of behaving badly - Guerrilla Girls (Group of artists) (Chronicle Books, 2020)
Guerrilla Girls: The Art of Behaving Badly is the first book to catalog the entire career of the Guerrilla Girls from 1985 to present. The Guerrilla girls are a collective of political feminist artists who expose discrimination and corruption in art, film, politics, and pop culture all around the world. This book explores all their provocative street campaigns, unforgettable media appearances, and large-scale exhibitions. Captions by the Guerrilla Girls themselves contextualize the visuals. Explores their well-researched, intersectional takedown of the patriarchy In 1985, a group of masked feminist avengers'known as the Guerrilla Girls'papered downtown Manhattan with posters calling out the Museum of Modern Art for its lack of representation of female artists. They quickly became a global phenomenon, and the fearless activists have produced hundreds of posters, stickers, and billboards ever since. More than a monograph, this book is a call to arms. This career-spanning volume is published to coincide with their 35th anniversary. Perfect for artists, art lovers, feminists, fans of the Guerrilla Girls, students, and activists You'll love this book if you love books like Wall and Piece by Banksy, Why We March: Signs of Protest and Hope by Artisan, and Graffiti Women: Street Art from Five Continents by Nicholas Ganz.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; artivisme; arts; arts visuels et médiatiques; com5170; corps; cours; discipline; histoire de l'art; justice sociale; militance; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; représentation des femme*; régions géographiques; sexisme; sofia; systèmes d'oppressions; thématiques; travail; états-unis

91-LGBT+ - Babin, Sylvette; Glenn, Clinton; Gayed, Andrew; Barbu, Adam; Williamson, Andrea; Varghese, Ricky; Flavelle, Genevieve (2017)
Dans la foulée du numéro précédent, qui portait sur les féminismes, ce dossier poursuit la réflexion sur la question des genres et des sexualités en s’attardant aux pratiques et aux théories qui cherchent à transcender la pensée binaire de la société patriarcale hétéronormative et cisnormative. On y explore notamment les stratégies déployées par les artistes afin de rendre visible les communautés LGBT+ et de faire entendre la multiplicité des voix en marge du régime patriarcal de production des savoirs.
Keywords: 2000 à aujourd'hui; LGBTQIA2+; amériques; approches et analyses; arts; arts visuels et médiatiques; canada; corps; cours; discipline; har4600; histoire de l'art; hétérosexisme; premier cycle; périodes historiques; queer; québec; ressource en ligne; régions géographiques; sexualité; systèmes d'oppressions; thématiques; transféminisme

Deer Woman: an anthology - LaPensée, Elizabeth; Alvitre, Weshoyot; Stonefish, Patty; Vasquez, Allie; Naragon, Rebecca; Thunder, Jonathan; Native Realities (Firm); Arming Sisters (Organization) (Native Realities, LLC, 2017)
Based on the true stories of Indigenous women throughout the world, Deer Woman: An Anthology is an extension of the Deer Woman: A Vignette, comic book that itself is a powerful expression and weaves the stories of Deer Woman into a modern narrative of the struggles of Indigenous women in North America. This anthology features the work of more than a dozen Native women sharing stories of survival, empowerment, and healing. Edited by Elizabeth LaPensée and Weshoyot Alvitre and featuring the work of: Patty Stonefish, Allie Vasquez, Mia Casesa, Darcie Little Badger, Tara Ogaick, Kimberly Robertson, Barbara Kenmille, Maria Wolf Lopez, Tatum Bowie, Jackie Fawn, Rebecca Roanhorse, Carolyn Dunn, Nashoba Dunn-Anderson, and more, this anthology is an important addition to the current conversation about violence against women, especially Native women.-from publisher's website.
Keywords: amérique du nord; amériques; approches et analyses; arts; arts visuels et médiatiques; bande-dessinée; care; cours; discipline; environnement; féminisme autochtone; histoire et politique; intersectionnalité; militance; pol4105; premier cycle; racisme; régions géographiques; sexisme; sofia; système colonial; systèmes d'oppressions; thématiques; violences; écoféminisme; études littéraires

Stitching through Silence: Walking With Our Sisters, Honoring the Missing and Murdered Aboriginal Women in Canada - Anderson, Stephanie G. (TEXTILE, 2016)
This article explores the complex relationship between processes of making, memory, healing, and social activism activated by Walking With Our Sisters, a large-scale commemorative installation intended to foster awareness for missing and murdered Indigenous women in Canada.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; art autochtone; art contemporain; artistes autochtones; arts; arts visuels et médiatiques; canada; cours; discipline; femmes* artistes; féminicide; féminisme autochtone; histoire de l'art; histoire et politique; militance; perlage; pol4105; premier cycle; périodes historiques; régions géographiques; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

Être féministe et objectifier son propre corps : les autoportraits d'Hannah Wilke - Institut de recherches et d'études féministes
Est-ce que c'est féministe de se mettre nue devant une caméra ? Comment peut-on jouer avec la caméra jusqu'à reprendre pouvoir sur notre image ? Amélie Fontaine-Dupont nous partage ses résultats de recherche sur l'artiste Hannah Wilke et montre comment l'auto-objectification sexuelle peut être une posture féministe et permettre d’approfondir la réflexion sur la culpabilisation et la répréhension des femmes qui font usage de leur corps et de leur sexualité à des fins d’émancipation. Biographie: Amélie Fontaine-Dupont est étudiante à la maîtrise en histoire de l'art à l'UQAM et détient un baccalauréat en histoire de l'art de l'Université Laval. S’intéressant autant aux études féministes qu’à l’art contemporain, ses recherches actuelles portent sur l'auto-objectification sexuelle comme forme d’agentivité et d’activisme féministe dans les œuvres performatives de l'artiste états-unienne Hannah Wilke. Amélie est membre étudiante de l'Institut de recherches et d'études féministes de l’UQAM et du Réseau québécois en études féministes. Elle occupe également le poste de responsable des communications de l'Association des cycles supérieurs en histoire de l'art de l'UQAM. En parallèle à ses études, elle travaille à la Galerie de l'UQAM et intervient ponctuellement en tant que médiatrice culturelle à l'occasion d'évènements artistiques et d’expositions. Enregistré durant la Tournée des cégeps à l’automne 2024 (https://iref.uqam.ca/babillard/tournee-des-cegeps-foire-feministe-feministes-dans-la-cite/)par Rajae Anys et Juliette Chevet. Ecrit et monté par Juliette Chevet. Avec le soutien financier du CRSH
Keywords: 1900-1999; 1970-1979; 1980-1989; amérique; approches et analyses; arts; corps; discipline; foire féministe; histoire de l'art; militance; patriarcat; régions géographiques; sexisme; systèmes d'oppressions; thématiques; états-unis

The Native and the Refugee - Peterson, Matt; Rasamny, Malek (The Native and the Refugee)
A multi-media project profiling the spaces of the Indian reservation and Palestinian refugee camp: spaces of exception whose position in the struggle for native and Palestinian autonomy are essential. The Native and the Refugee will culminate in a feature-length documentary film.
Keywords: afrique; amérique du nord; amériques; approches et analyses; arts; arts visuels et médiatiques; camps de réfugiés; cours; discipline; documentaire; gaza; justice sociale; militance; palestine; pol5480; premier cycle; ressource en ligne; régions géographiques; système colonial; systèmes d'oppressions; thématiques; violences

Marguerite : la traversée | Épisode 2 - Transistor média
Émilie Monnet trace des parallèles entre la vie de Marguerite Duplessis et la cause des femmes, et plus particulièrement des femmes autochtones. Accompagnée de ses invité·e·s, Émilie parle de la tragédie des femmes disparues et de l’objectification dont elles sont encore victimes aujourd’hui,...
Keywords: 1700-1799; 2000 à aujourd'hui; 2010-2019; 2020-2029; amériques; approches et analyses; arts; arts visuels et médiatiques; canada; cours; discipline; esclavage; féminisme autochtone; histoire et politique; justice sociale; martinique; performance; premier cycle; périodes historiques; québec; racisme; régions géographiques; sex2283; sexisme; système colonial; systèmes d'oppressions; thématiques; trafic sexuel; traite des femmes; violences; études littéraires